General introduction to altitude adaptation and mountain sickness - Bärtsch, P.; Saltin, B. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The key elements in acclimatization aim at securing the oxygen supply to tissues and organs of the body with an optimal oxygen tension of the arterial blood. In acute exposure, ventilation and heart rate are elevated with a minimum reduction in stroke volume. In addition, plasma volume is reduced over 24-48 h to improve the oxygen-carrying capacity of the blood, and is further improved during a prolonged sojourn at altitude through an enhanced erythropoiesis and larger Hb mass, allowing for a partial or full restoration of the blood volume and arterial oxygen content. Most of these adaptations are observed from quite low altitudes [~1000 m above sea level (m a.s.l.)] and become prominent from 2000 m a.s.l. At these higher altitudes additional adaptations occur, one being a reduction in the maximal heart rate response and consequently a lower peak cardiac output. Thus, in spite of a normalization of the arterial oxygen content after 4 or more weeks at altitude, the peak oxygen uptake reached after a long acclimatization period is essentially unaltered compared with acute exposure. What is gained is a more complete oxygenation of the blood in the lungs, i.e. SaO2 is increased. The alteration at the muscle level at altitude is minor and so is the effect on the metabolism, although it is debated whether a possible reduction in blood lactate accumulation occurs during exercise at altitude. Transient acute mountain sickness (headache, anorexia, and nausea) is present in 10-30% of subjects at altitudes between 2500 and 3000 m a.s.l. Pulmonary edema is rarely seen below 3000 m a.s.l. and brain edema is not seen below 4000 m a.s.l. It is possible to travel to altitudes of 2500-3000 m a.s.l., wait for 2 days, and then gradually start to train. At higher altitudes, one should consider a staged ascent (average ascent rate 300 m/day above 2000 m a.s.l.), primarily in order to sleep and feel well, and minimize the risk of mountain sickness. A new classification of altitude levels based on the effects on performance and well-being is proposed and an overview given over the various modalities using hypoxia and altitude for improvement of performance.